Hubungan Antara Implementasi Strategi Pembelajaran Direct Instructional menggunakan Google Classroom dan Motivasi Belajar terhadap Hasil Belajar Siswa untuk Mata Pelajaran Administrasi Sistem Jaringan di Jurusan Teknik Komputer dan Jaringan SMK Negeri 2 S - Aji Irvansyah; Admaja Dwi Herlambang; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In online learning situations, appropriate learning strategies are needed to deliver learning materials to students and how to motivate students when carrying out online learning. This research is a quantitative type of causality analysis. This study seeks to find out the relationship between direct instructional learning strategies and learning outcomes, the relationship between learning motivation and learning outcomes, and the relationship between direct instructional learning strategies and learning motivation together on learning outcomes. The data collection method used a questionnaire that was distributed and filled out online. The number of respondents was 131 students majoring in Computer and Network Engineering at SMKN 2 Singosari. This study uses the product moment correlation test to prove the hypothesis. The results showed that (1) there was no positive and significant relationship between direct instructional learning strategies and learning outcomes based on a significance value of 0.414 > 0.05; (2) there is no positive and significant relationship between learning motivation and learning outcomes based on a significance value of 0.798 > 0.05; (3) there is no positive and significant relationship between direct instructional learning strategies and learning motivation with learning outcomes based on a significance value of 0.702 > 0.05.